Comparative analysis between extra‐short implants (≤6 mm) and 6 mm‐longer implants: a meta‐analysis of randomized controlled trial. (17th February 2022) - Fernandes, GVO; Costa, BMGN; Trindade, HF; Castilho, RM; Fernandes, JCH
ABSTRACT: The goal of this systematic study was to compare the survival rate (SR), marginal bone loss (MBL) and clinical complications between extra‐short implants (≤6 mm) and 6‐mm‐longer implants in randomized clinical trials. A systematic electronic and manual search was performed using the PubMed, Web of Science, Scopus and DOAJ databases. A meta‐analysis was conducted to compare the SR and MBL between both groups. We have selected 17 studies out of 1016 articles for qualitative and quantitative analysis. The data from 956 patients and 1779 implants were used with an overall mean clinical follow‐up of 3.88 years ranging from 1 to 8 years. Overall, the SR of extra‐short implants (93.12%) was lower than the observed in 6‐mm‐longer implants (95.98%); however, there was no statistical significance on these findings ( P  > 0.10). MBL analysis showed that extra‐short implants and the 6‐mm‐longer group presented an average of −0.71 and −0.92 mm after 1‐year respectively. Three years follow‐up showed MBL of −0.42 mm (≤6 mm) and −0.43 mm (>6 mm); 5 years follow‐up showed an MBL of −0.69 mm (≤6 mm) and −0.46 mm (>6 mm); and after 8 years of follow‐up, it was found an MBL of −1.58 mm (≤6 mm) and −2.46 mm (>6 mm). Within the limitation of this study, the results indicated that SR of extra‐short implants was similar to 6‐mm‐longer implants. In contrast, MBL and the presence of clinical complications were observed at a lessened rate on extra‐short implants.